AI and Human-AI Collaboration in Financial Reconciliation Systems - Naveen Kumar Dodde Gowda, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article examines the evolution and impact of human-AI collaboration in financial reconciliation systems, focusing on how artificial intelligence technologies are transforming traditional reconciliation processes while maintaining crucial human oversight. The article explores the current landscape of financial reconciliation, the implementation of AI systems, the critical role of human expertise, and the measurable benefits of human-AI collaboration. The article investigates pattern recognition capabilities, automated data processing, strategic oversight, and exception handling, demonstrating how the synergy between human judgment and AI capabilities enhances accuracy, efficiency, and risk management in financial operations. The article also addresses implementation considerations, including technical requirements and change management strategies necessary to deploy AI-powered reconciliation systems successfully.
Keywords: Financial Reconciliation; Artificial Intelligence; Human-AI Collaboration; Pattern Recognition; Change Management